Optimal scalable redeployment algorithm of relay nodes in wireless sensor networks - Bin ZENG; Jun WEI; Lu YAO (Tongxin xuebao)
A relay node redeployment algorithm was proposed to find the optimal location of redeployment relay node when an existed relay node was overloaded considering the multi-dimensional localization and bandwidth constraint.The algorithm translated the redeployment problem into the optimal location planning in a multi-dimensional Euclidean space and then gave the suitable redeployment plan through searching the intersections of transmission areas heuristically.The correctness and completeness of the algorithm were proved.Furthermore,an optimization method was proposed to reduce the complexity of the algorithm to the linear function of the number of sensor nodes.The simulation results show that the algorithm can balance the loads of the overloaded relay nodes by joining in the candidate nodes and then prolong the network lifetime.